KONSEP PENILAIAN BAGI PARA PAMONG BELAJAR DALAM RANGKA PENGENDALIAN MUTU DAN DAMPAK PROGRAM PNF - Ma’ruf Akbar (Direktorat Pembinaan Guru dan Tenaga Kependidikan Pendidikan Anak Usia Dini Kementerian Pendidikan dan Kebudayaan bekerjasama dengan Fakultas Ilmu Pendidikan Universitas Negeri Jakarta, 2007)
Learning mentor has an important role in implementing NFE programs, especially as a technical functional operator, learning model developer, instructor and evaluator. They should be able to do the evaluation in order to control the quality and the implementation impact of NFE programs. NFE provides educational services which have to be improved continuously in the aspects of planning, implementation, learning achievment and the outcome.